PENGARUH LITERASI KEUANGAN DAN RISK ATTITUDE TERHADAP KEPEMILIKAN ASURANSI JIWA - Cindy Wahono; Pwee Leng (Business Administration Department - Universitas Katolik Parahyangan, 2022)
Public understanding of insurance ownership is proven to be shallow, which can be seen from the low insurance literacy index in Indonesia. The same thing is also shown by the small number of people who already have insurance at a young age. Insurance ownership is also influenced by people's attitudes toward reducing and managing risk. This study aims to examine the effect of financial literacy and risk attitude on life insurance ownership. This study is an associative research by taking 124 respondents who own life insurance. Data was collected through a google form questionnaire and processed using a Likert scale. The data were then analyzed by logistic regression IBM SPSS Statistics 18. The results showed that financial literacy had a significant effect on life insurance ownership, while risk attitude had no significant effect on life insurance ownership. Risk Attitude has no effect on insurance ownership because people prefer low premium values. On the other hand, insurance ownership can still be increased by increasing public awareness of the uses and benefits of insurance, especially for planning and managing personal finances.